Analisis Keefektifan Kalimat dalam Bunga Rampai Kumpulan Opini Menuju Indonesia Sehat dan Penerimaan Negara yang Optimal melalui Reformasi Kebijakan Cukai Tembakau: Masukan untuk Penyusun RPJMN 2025-2029 - Riska Rahmawati; Mega Ananda Pratiwi; Efra Elya; Puspita Wijayanti; Vivia Rahmawati; Siti Hajizah; Asep Purwo Yudi Utomo; Eko Ahmad Riyanto (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
An Anthology of Opinions Towards a Healthy Indonesia and Optimal State Revenue through Tobacco Excise Policy Reform contains ideas related to tobacco excise policy in supporting public health and optimizing state revenue. This study aims to analyze the effectiveness of sentences in a collection of opinion pieces about a healthy Indonesia and optimal state revenue through tobacco excise policy reform. In conducting the research, the authors used a methodological approach in the form of a qualitative descriptive method. Data collection with this method is done using reading and recording techniques. This research uses text analysis techniques with a qualitative descriptive analysis approach as a data analysis technique. Based on the analysis that has been carried out on Bunga Rampai Collection of Opinions Towards a Healthy Indonesia and Optimal Revenue through Tobacco Excise Policy Reform, 11 effective sentences have been found. Meanwhile, errors related to EYD and KBBI were also found with details in the form of 16 ineffective sentences, 31 ambiguous sentences, 5 sentences with capitalization errors, 12 sentences with nonstandard words, and 18 sentences with other types of errors. In addition to being used as a reference for analyzing sentence effectiveness, this research is also useful for enriching the study of tobacco excise policy communication, especially for RPJM 2025-2029 policymakers. In addition, this research can also be used as a reference for further research related to sentence effectiveness.